Inelastic Displacement Ratios for Evaluation of Degrading Peak - Oriented SDOF Systems - Borekci, Muzaffer; Kircil, Murat S.; Ekiz, Ibrahim (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2018)
Estimation of the inelastic displacement demand (IDD) is an important part of the performance-based design. Coefficient method is one of the methods for the estimation of IDD and in this method, IDD is determined by multiplying elastic displacement demand with inelastic displacement ratio (C-R). Previous researches showed that structures deteriorate and also exhibit dynamic instability under severe earthquakes and these behaviors should be considered in the estimation of C-R to estimate a reliable IDD. In this study, C-R of the non-degrading bilinear hysteretic model and the degrading peak-oriented hysteretic model with collapse potential were determined and effects of degradation on IDD were investigated. Nonlinear time history analysis of SDOF systems were performed using considered hysteretic models. Furthermore a new equation is proposed for the mean C-R of degrading SDOF systems. Also, effect of local site conditions and post-yield stiffness on the mean C-R of degrading SDOF systems were investigated.
Keywords: inelastic displacement ratio; nonlinear response; degradation; dynamic instability; collapse; STRUCTURAL SYSTEMS; DESIGN SPECTRA; STRENGTH; INSTABILITY; Engineering